The Influence of Government Expenditure and Regional Economic Growth on The Human Development Index in Districts and Cities In Jambi Province 2019-2021 - Syafrul Antoni (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
This research aims to analyze how much influence regional government spending and economic growth have on the human development index in districts and cities in Jambi Province. The data used is Time Series data for the 2019-2021 period. This research was conducted using quantitative methods using panel data regression analysis. The data came studied from 11 regional governments (districts and cities) located in Jambi Province over a period of 3 years (2019-2021). This data was obtained from the district and city Central Statistics Agency and from several related agencies. The data was then analyzed using the multiple regression method. Data calculations in this research used the SPSS program. The research results show that the regional government expenditure variable (X1) does not have a positive and significant effect on the human development index in districts and cities in Jambi province. Meanwhile, the economic growth variable (X2) also does not have a positive effect on the district and city human development index in Jambi province.